PENGARUH BEBERAPA TARAF KONSENTRASI BA TERHADAP MULTIPLIKASI TUNAS CINCAU HITAM (Mesona palustris) IN VITRO - Miftakhurohmah, Miftakhurohmah; Syahid, Sitti Fatimah (Buletin Penelitian Tanaman Rempah dan Obat, 2006)
Mesona palustris is one of the medi-cinal plant which is potential to be developed. Recently, the agribisnis of this plant commo-dity is considered to be potential. To supportÂ  the availability of plant material, propagation by tissue culture technique being a good alternative for mass production. This expe-riment was conducted from January to April 2005 at the Tissue Culture Laboratory of Indonesian Spices and medicinal Crops Research Institute (ISMECRI) in Bogor. The objective of this research was to find out the effect of several concentrations of BA on shoot multiplication of Mesona palustris. The treatments tested were several concentrations of BA e.g. : 0.0 ( control); 0.2 ; 0.4; 0.6; and 0.8 mg/l. Experiment was arranged in a com-pletely randomized design with six replica-tions. The parameters observed were number of shoots, length of shoots, number of leaves, and percentage of rooting shoots, at 3, 5, and 9 week after culture (WAC). The result showed that the use of 0,2 mg/l BA performed the best shoots growth multiplication with a relatively high rate of increased shoots num-ber and percentage of rooting shoots, at 3 to 9 WAC. Abundant shoots number (21.00 shoots), with length of shoots of 5.92 cm, leaves number of 13.00, and percentage of rooting shoots of 83.33% was obtained on MS + BA 0.2 mg/l, 9 WAC.Â